Perceived Training Needs of Farmers in Pearl Millet Cultivation - Jangid, B L; Chand, Khem; Rao, S S; Singh, Y V (Annals of Arid Zone, 2016)
The present investigation was undertaken during the 2000-0 I in two villages of Pali district of semi-arid Rajasthan, to tind out the training needs of the farmers for improved practices of pearl millet cultivation and their opinion about the time, duration and place for organizing training programs. Simple random sampling method was used to draw a study sample of 120 respondent famlers, who were actively engaged in farming. Personal interview technique by using a pre-tested schedule was used for collection of the data. Results show that most of the famlers needed medium level of training for improved practices of pearl millet cultivation. The order of importance of training needs of the farmer was crop diseases and control, insect pests and control, seed treatment, use ofbio-fertilizers, improved varieties, soil and water testing, storage using chemical pesticides, use of nitrogenous fertilizers, use of phosphatic fertilizers minimum support price of crop and use of government storage facility. Farmers opined that training program should be organized before sowing of crop (6I’Vo) should be, of two days duration (59%) and conducted both on and off campus (44%).